The Economic Rationales behind the Un-Doubtful Riba - Alzubi, Abdelmonem (2008)
The proscription of riba embodies the corner stone of Islamic economics. Closing the door of Ijtihad and the resulting superficial analysis of riba has fashioned a widespread perception equalizing interest with riba (al-Sanhouri, 1954, 1955; Kuran, 2005). Factually, the resulting unique focus on interest has tightened the number of studies attempting to tackle the issue of riba logically in modern basis. In order to contribute in this context, the dissertation aims at pointing out methodically the economic rationales behind riba al-jahiliyya in the modern perspective. Furthermore, the widespread view bearing in mind interest or excessive interest as the unique major rationale behind credit indulgent with this sort of riba will be critically evaluated. The explicit focus on riba al-jahiliyya does not imply any ignorance of other forms of riba. In point of fact, the dissertation will afford a thorough literature review of riba al-nasia and riba al-fadl to justify that these sorts of riba are prohibited to avoid hardship which riba al-jahiliyya symbolizes its extremist version. In order to attain its objectives, the dissertation employs a modern mortgage model designed by Ebrahim and Ahmed (2007) to generate different default simulations which will most likely pilot to riba al-jahiliyya. In addition, by driving the same model to the interest free mode, the widespread perception considering interest as the unique major dynamic behind riba al-jahiliyya is critically evaluated. Afterwards, the results achieved from the simulations are justified using the modern Islamic and un-Islamic literature. The dissertation ends by the conclusion that excessive credit risk and unpredictable economic shocks are of the chief rationales behind riba al-jahiliyya at our time. Moreover, the dissertation ends by the view that neither interest nor excessive interest stands uniquely behind credit indulgent with this sort of riba.